Principles of brain evolution - Striedter, Georg F. (Sinauer Associates, 2005)
Brain evolution is a complex weave of species similarities and differences, bound by diverse rules or principles. This book is a detailed examination of these principles, using data from a wide array of vertebrates but minimizing technical details and terminology. It is written for advanced undergraduates, graduate students, and more senior scientists who already know something about "the brain," but want a deeper understanding of how diverse brains evolved.